Pentingnya Penanaman Nilai-Nilai Etika Di Tengah Era Digital - Elim Halimatusadiyah (Jurnal Manajemen dan Pendidikan Agama Islam, 2023)
Another term for "character education" can be expressed as "Moral Formation" or "Ethical Guidance." This refers to the effort to develop and shape attitudes, moral values, and ethics in students through knowledge and guidance from various parties such as parents, teachers, and the community. The crucial roles of parents, teachers, and the community in shaping a child's character cannot be overlooked. Each child possesses inherent goodness that needs to be nurtured and socialized effectively to ensure optimal character development. In this digital age, especially among high school student, the use of digital media is prevalent. Educators, parents, and responsible adults in the community have the responsibility to guide and monitor children's use of digital media. While the digital era brings positive impacts, the existence of negative effects demands special attention. Therefore, efforts are required to ensure that children can use digital media wisely, allowing them to reap positive benefits for themselves and their lives